Political Competition, Ideology and Corruption - Aristotelis Boukouras; Kostas Koufopoulos (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
This paper presents a model of political competition, where voter decisions are affected by their ideological adherence to political parties. We derive a number of interesting results: First, we show that an equilibrium exists even though voting is fully deterministic. Second, although politicians, because of deterministic voting, can win an election with certainty by making concessions to voters, they choose to win the election only with some probability in order to maximize their expected rents. Third, if the distribution of ideology is asymmetric, then political parties follow different platforms in equilibrium. Finally, our model generates two novel empirical predicitions, which, to the best of our knowledge, have not been tested yet: i) the higher the ideological adherence to a political party the more inefficient policies this party will follow, ii) the higher the number of extra votes required for election victory (the super-majority requirement) the higher the degree of corruption.
Keywords: G21; G28; H32; P16; P43; 330; corruption; political instability; voting behavior